2022
DOI: 10.1016/j.acra.2021.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Radiology Residency Selection Process: A Survey of Radiology Residency Programs in the US

Abstract: Objective Virtual residency interviews have become crucial in maintaining CDC-recommended precautionary measures throughout the ongoing COVID-era. However, scant literature exists regarding the direct impact the pandemic has had on the radiology program selection process, including preferred modalities of residency interviews and social media utilization. This survey aimed to understand how radiology programs adapted to changes in the 2020-21 virtual application cycle. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…Individual free text comments also varied with positive, neutral, and negative responses regarding V-Int. This result differs from other recently reported surveys of residency directors who found V-Int more favorable and successful [ 5 , 10 ]. Respondents in our study were mixed about the future of V-Int.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Individual free text comments also varied with positive, neutral, and negative responses regarding V-Int. This result differs from other recently reported surveys of residency directors who found V-Int more favorable and successful [ 5 , 10 ]. Respondents in our study were mixed about the future of V-Int.…”
Section: Discussioncontrasting
confidence: 99%
“…The averaged preference of musculoskeletal radiology fellowship directors would be to have them comprise 40.6% of interviews in the future under ideal conditions. This finding is similar to the reticence to continue a full virtual format in other surveys of residency directors [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Fears that virtual interviews preclude full candidate assessment or communication of program attributes may be unfounded. Studies of the virtual interview process found that programs perceived they could present themselves and their program and assess applicant candidacy virtually [ 20 , 28 ]. During the pandemic, many institutions increased their social media presence to enrich the presentation of their program [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,12,22,30,31 Despite these reports, other studies demonstrated that implementation of virtual interviews effectively met overall program and applicant goals without significant differences in interview outcomes, including candidate and program assessment, ranking, and matching. 1,11,20,21,33,41,42 Despite their many limitations, these studies suggest that virtual interviews were generally wellreceived, and both programs and applicants appear to favor a hybrid interview model for the future. 1,9,16,21,22 However, no studies have yet compared hybrid models to in-person-only or virtualonly models.…”
Section: Challenges and Mitigation Strategiesmentioning
confidence: 91%